La bella mugnaia a Zurigo: sul piacere del falso ascolto in Christoph Marthaler - Wiesel, Jörg (Kritik. Rivista di letteratura e critica culturale, 2024)
The subject of this essay is the theatrical art of Marthaler. The works of the director and his team seduce through careful, perhaps deconstructive (and capable of equivocation) reading, through the unobtrusive and loving way of reflecting, critiquing and deconstructing theatrical and musical traditions that retain great popularity to our present day. The theatricalization of misunderstanding (in listening and reading) is in Marthaler an offering of enjoyment.